Attitudinal factors affecting the adoption of internet banking services among small and medium enterprises in Yemen - Al-Fahim, Nabil Hussein; Wan Jusoh, Wan Jamaliah; Adewale, Abideen Adeyemi (2015)
In spite of the wide adoption of Internet banking service in developed countries, its application is still low in developing countries like Yemen. The purpose of this study is to examine and investigate the main factors which influence the adoption of Internet banking services by Small and Medium Enterprises (SMEs) managers or owners in Yemen. The research framework consists of sex latent variables, five exogenous variables and one endogenous variable. The exogenous variables consist of attitudinal factors such as perceived usefulness, ease of use, trust, risk and awareness while endogenous variable comprises of intention towards Internet banking service adoption (IBSA). In addition, this study will explain how the Technology Acceptance Model (TAM) was being used in examining the factors of Internet banking services adoption in Yemen. The hypothetical relationship was examined using structural equation modeling (SEM). The findings of the study indicated that perceived usefulness was the high predictor that influence towards IBSA followed by ease of use and awareness while perceived risk and trust are insignificant and negative effect towards IBSA in Yemen. This study also emphasized on the role of organization type (trading and services) as significant moderator in the adoption of IB; this means trading organizations are willing to adopt IB more than services organizations.